การวิเคราะห์จำนวนรถขนส่งสินค้าของตัวเองภายใต้ความไม่แน่นอน - ภควัต นาคเสน (จุฬาลงกรณ์มหาวิทยาลัย, 2014)
The aim of this thesis is to develop a tool for determining the proper number of private trucks under uncertain demand. The data had been collected from large publishing company which usually use their own private trucks together with subcontractor trucks. This thesis has used the Spreadsheet program for creating different shipping scenarios. The tool consists of 4 modules; the simulation of daily transportation demand, the estimation of the number of trucks to be used each day base on a regression model with delivery demand and inter-customer distance being explanatory variables, the estimation of transportation cost including cost of private trucks and cost of subcontractors trucks, lastly, the determination of appropriate number of private trucks under uncertainty applying Sensitivity Analysis